Papilomatose respiratória recorrente em adultos: uma revisão de escopo - BEZERRA, Andressa Lima Castro (2026)
Introduction: Recurrent respiratory papillomatosis is a rare and chronic condition characterized by benign papillomatous lesions in the respiratory tract, commonly associated with human papillomavirus (HPV) genotypes 6 and 11. Adult-onset disease presents a variable clinical course, with frequent recurrence and significant functional impact. Objective: To map the available scientific evidence on adult-onset recurrent respiratory papillomatosis, focusing on epidemiological, clinical, and therapeutic aspects. Methods: This scoping review was conducted in accordance with the Joanna Briggs Institute (JBI) methodology and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) extension (Tricco et al., 2018). Searches were performed between July and September 2025 across PubMed/MEDLINE, Embase, Scopus, Web of Science, Cochrane Library, LILACS, ProQuest, and Google Scholar, yielding 2,079 records. Study selection was performed in two stages, followed by standardized data extraction. Results: The included studies were predominantly observational, mainly conducted in tertiary care settings, and characterized by small to moderate sample sizes. Adult-onset recurrent respiratory papillomatosis predominantly affected young to middle-aged males. Clinically, the disease was marked by dysphonia, frequent recurrence, and the need for repeated surgical interventions. Surgical management remained the cornerstone of treatment, while adjuvant therapies, such as bevacizumab and cidofovir, showed potential benefits despite heterogeneous and limited evidence. Conclusion: The current evidence on adult-onset recurrent respiratory papillomatosis remains fragmented and predominantly observational, with significant gaps in population- based epidemiology, standardized outcomes, and comparative therapeutic effectiveness. There is a need for multicenter studies with robust methodological designs, as well as clinical validation of emerging therapeutic strategies, including immunotherapy and HPV vaccination approaches, which may contribute to reducing recurrence rates and improving patient outcomes.